Ehrlich Ascites Tumor Preservation for Fifteen Years—a Simple Method - Cassel, William A. (1974)
The Ehrlich ascites tumor was preserved for 15 years by adding to it an equal volume of 40% glycerol and placing the preparation directly into a freezer at -60 C.